Women in sustainable development : empowerment through partnerships for healthy living - Vargas, Claudia Maria (2002)
Explores how some women advance sustainable development through partnerships. Examines the kinds of collaborative relationships that women's groups have forged with public, private, nonprofit or nongovernmental organizations to create and engage in sustainable activities. Presents a case study of a women's grassroots organization, COFERENE in San Ramon, Costa Rica and considers the various partnerships it has created to advance the organization's mission.